2017
DOI: 10.1016/j.gr.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Pamir Plateau formation and crustal thickening before the India-Asia collision inferred from dating and petrology of the 110–92 Ma Southern Pamir volcanic sequence

Abstract: The formation of the Pamir is a key component of the India-Asia collision with major implications for lithospheric processes, plateau formation, land-sea configurations and associated climate changes. Although the formation of the Pamir is traditionally linked to Cenozoic processes associated with the IndiaAsia collision, the contribution of the Mesozoic tectonic evolution remains poorly understood. The Pamir was formed by the suturing of Gondwanan terranes to the south margin of Eurasia, however, the timing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 84 publications
0
38
0
Order By: Relevance
“…3) and in the Kyzylrabot area, mid-Cretaceous (ca. 105 Ma) volcanic rocks were deposited unconformably on Jurassic carbonate rocks (Aminov et al, 2017;Chapman et al, 2018; this study) (Fig. 4).…”
Section: Cretaceous Tectonics In the South Pamir Terranementioning
confidence: 81%
See 2 more Smart Citations
“…3) and in the Kyzylrabot area, mid-Cretaceous (ca. 105 Ma) volcanic rocks were deposited unconformably on Jurassic carbonate rocks (Aminov et al, 2017;Chapman et al, 2018; this study) (Fig. 4).…”
Section: Cretaceous Tectonics In the South Pamir Terranementioning
confidence: 81%
“…4, 5K, and 5L), as the age of the volcanic units in the Kyzylrabot area were recently reclassified from Paleogene(?) to mid-Cretaceous (Aminov et al, 2017;Chapman et al, 2018).…”
Section: Age Of the Mamazair Conglomerate And Murghab Basin Stratamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, based on geochemical data, it has been demonstrated that the Cretaceous magmatic intrusions represent the development of an Andean‐style arc along the southern Eurasian margin due to the northward subduction of the Neotethys ocean (Figure b; for example, Chapman, Scoggin, et al., ; Faisal et al., ; Kapp, DeCelles, Gehrels, Heizler, & Ding, ; Robinson, ; Schwab et al., ). This magmatism occurred from 130 to 95 Ma in the Karakoram (Aminov et al., ; Debon, Le Fort, Dautel, Sonet, & Zimmermann, ; Fraser et al., ; Heuberger et al., ; Robinson, ), and to 105 Ma in the North Lhasa (Tibet; Chen et al., ; Sui et al., ; Zhu et al., ), with a high‐flux event between 110 and 105 Ma. It is noteworthy that the high‐flux event overlaps the important concentration of monazite ages between 105 and 85 Ma from our study and also the Cretaceous monazite ages reported in the Karakoram Metamorphic Complex (Figure b; Fraser et al., ; Streule et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…This allows the direct study of the tectonic evolution of metamorphic and magmatic rocks residing at mid‐crustal conditions, and the crustal foundering that affected its root zone during this time (Hacker et al., ; Kooijman, Smit, Ratschbacher, & Kylander‐Clark, ), especially in the Central Pamir and Karakoram blocks (Fraser, Searle, Parrish, & Noble, ; Mahéo, Blichert‐Toft, Pin, Guillot, & Pêcher, ; Palin, Searle, Waters, Horstwood, & Parrish, ; Rolland, Mahéo, Guillot, & Pêcher, ; Rolland, Villa, Guillot, Mahéo, & Pêcher, ). Only a few studies, however, have examined the detailed timing of deformation and metamorphism in the South Pamir, including the Hindu Kush region, which has been shown to preserve a potentially more complex and longer history of magmatism and metamorphism than the adjacent Karakoram block (Aminov et al., ; Chapman, Robinson, et al., ; Chapman, Scoggin, et al., ; Faisal, Larson, Camacho, & Coutand, ; Faisal, Larson, Cottle, & Lamming, ; Faisal, Larson, King, & Cottle, ; Hildebrand, ; Hildebrand, Noble, Searle, Waters, & Parrish, ; Hildebrand, Searle, Shakirullah, Khan, & Van Heijst, ).…”
Section: Introductionmentioning
confidence: 99%